Economic analysis of current trends of attracted foreign direct investment in Kazakhstan (Journal of Economic Research & Business Administration, 2018)
To form a competitive national economy, it is absolutely necessary to develop an effective investmentmanagement system. Due to this, the authors attempted to investigate the process of attracting aflow of foreign direct investment (FDI) to Kazakhstan. Analytical data of the Committee on Statistics ofthe Republic of Kazakhstan and the UN Committee on Trade and Development were used for analysis.In addition, the article also considers the attraction of FDI in the CIS region. A meaningful analysis of thedata made it possible to identify priority sectors that are of interest to foreign investors in the economy ofKazakhstan, as well as projects that contribute to the growth of FDI in the republic. The authors believethat it is necessary to implement the most effective investment policy, which, on the one hand, contributesto the development of the scientific and engineering potential of the country, the development ofsmall and medium-sized businesses, and on the other hand, is aimed to ensure innovative developmentof industries and regions, to strengthen the infrastructure of innovation clusters . The practical significanceof this analysis is to ensure a favourable investment climate and to identify ways to improve theregulation of investment flows in Kazakhstan.